2019
DOI: 10.3390/cosmetics6020025
|View full text |Cite
|
Sign up to set email alerts
|

Use of Vegetable Oils to Improve the Sun Protection Factor of Sunscreen Formulations

Abstract: Some vegetable oils have many biological properties, including UV-absorbing capacity. Therefore, their use has been suggested to reduce the content of organic UV-filters in sunscreen products. In this work, we investigated the feasibility of developing oil-based vehicles with a high sun protection factor (SPF) using pomegranate oil (PMG) and shea oil (BPO) in association with different percentages of organic UV-filters (octyl– methoxycinnamate, butyl methoxydibenzoylmethane, and bemotrizinol). We characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…Oil and aqueous formulations have been proven to control frosty pod rot caused by Moniliophthora roreri on cocoa (Crozier et al 2015), finding that an inverted corn oil formulation significantly enhanced cocoa yield, providing a promising model for optimizing Trichoderma-based biocontrol strategies. Finally, some vegetable oils are able to absorb UV radiation (Montenegro and Santagati 2019) suggesting the possibility to use them as UV blockers.…”
Section: Oil Formulationsmentioning
confidence: 99%
“…Oil and aqueous formulations have been proven to control frosty pod rot caused by Moniliophthora roreri on cocoa (Crozier et al 2015), finding that an inverted corn oil formulation significantly enhanced cocoa yield, providing a promising model for optimizing Trichoderma-based biocontrol strategies. Finally, some vegetable oils are able to absorb UV radiation (Montenegro and Santagati 2019) suggesting the possibility to use them as UV blockers.…”
Section: Oil Formulationsmentioning
confidence: 99%
“…The cosmetic industry has benefited from the shea tree products as one of the best anti-ageing and moisturizing agents for the skin with sun-screening and collagen boosting properties (Suter et al 2016; Montenegro and Santagati 2019 ). The African melon ( Acanthosicyos horridus and Citrullus lanatus ) has been reported to have great potential in both the food and cosmetic industry (Houdegbe et al 2016 ; Cheikhyoussef et al 2017 ), while the emulsifying capacity of biosurfactants from quinoa has been reported as suitable for incorporation into cosmetic emulsion formulations (Bezerraa et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…were tested in vitro (Jarzycka et al, 2013) and authors obtained SPF value 26.61 ± 0.10. Pervious study found the vegetable oil such as pomegranate oil and shea oil showed the UV protection effect (Montenegro and Santagati, 2019) but those oils were not found in Melientha extract and its fractions. By the studied of Caddeo et al, 2018 found that vitamin E show UV protection activity by antioxidant effect and improve skin regeneration (Caddeo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%